Research on control strategy of a multi-energy ship microgrid using diesel–battery rotation - Weiqiang Liao; Longhai Xiao; Fuzhong Zhang; Meiqian Chen; Shixian Lin (Energy Reports, 2022)
As an object of this paper, a multi-energy ship microgrid system is considered, according to the ship operation conditions and energy saving and emission reduction requirements. A rotational control scheme for a diesel generator and an energy storage device is proposed, which can achieve both grid-tied and off-grid control. Firstly, taking into account the characteristics of small capacity microgrid and AC load, a topology of ship AC microgrid is adopted, based on the state of charge (SOC) and net load, construct a power coordinated control strategy by which diesel generators and energy storage systems can be alternately used as the main power supply for the microgrid; Secondly, for different power supply modes, a dual-mode switching technology based on V/F control and PQ control is proposed, and a significant improvement has been made in the performance of the voltage and current loop. Lastly, using the topology of the ship’s AC microgrid, a model for simulation is built according to the proposed diesel–battery rotation strategy and dual-mode switching technology, and the four operating modes involved in ship operation are simulated and laboratory verified. According to the results, the control strategy designed is both feasible and effective.